(untitled) (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2019)
The article is devoted to problems of trust in state, political and public institutions. In this article maked analysis of the concepts "trust", "interpersonal trust", "political trust". Specialists in different scientific fields take scientific and research interest in trust, due to this we can observe a wide spectrum of understandings and views towards trust nature, functions and trust investigation results application area. This article is devoted to the description of investigation best practices of trust, structural phenomenology of trust term, types of trust relationship and their perspectives, models of trust. This article is a full-fledged analysis of existing political researches; it discloses current issues of the topic and helps to determine ways and perspectives of further investigations of this concept.